Iraqi ports and their impact on the strength of the stat the Grand Faw Port as a model - Fayyad, Ahlam Ahmed Issa (The International and Political Journal, 2025)
Iraqi seaports have geostrategic importance as they are the economic outlet of Iraq to the outside world, especially foreign trade, especially the export of oil, which represents the lifeline of Iraq. Through their location, Iraqi ports have been given special military importance after external threats and dangers from the sea. Therefore, the research focused on studying the classification of Iraqi ports, focusing on the importance of ports from many aspects due to their international, regional and then local importance, to highlight the role of ports in the strength of the state, as seas and oceans have been used since ancient times as theaters of fighting and conflict, and are considered an offensive military force and a defensive military force. Iraqi ports are of great importance, especially after the developments witnessed by the region in terms of politics and economics, which places a great burden on the ports, which requires their study and development in order to be able to stand firmly in the face of regional and international challenges competing in the markets. The Grand Faw Port is a strategic project that will fundamentally change the geopolitical situation in Iraq, as Iraq is no longer suffocated by the sea, but will open up to space, and give strength to the state in Iraq .